Pengaruh Komponen Kualitas Pelayanan Terhadap Kepuasan Debitur Produk Kur : Studi Kasus pada PT Bank BNI (TBK) KC Bandung - Ading Rahman Sukmara; Dian Nugraha; Ferey Herman (Universitas Kristen Indonesia Toraja, 2024)
The problems faced in this study include (1) How does the service quality component influence in terms of direct evidence (tangibles) on the satisfaction of KUR product debtors at PT Bank BNI (TBK) KC Bandung? (2) How does the service quality component influence in terms of reliability on the satisfaction of KUR product debtors at PT Bank BNI (TBK) KC Bandung? (3) How does the service quality component influence in terms of responsiveness on the satisfaction of KUR product debtors at PT Bank BNI (TBK) KC Bandung? (4) How does the service quality component influence in terms of assurance on the satisfaction of KUR product debtors at PT Bank BNI (TBK) KC Bandung? (5) How does the service quality component influence in terms of empathy on the satisfaction of KUR product debtors at PT Bank BNI (TBK) KC Bandung? (6) How do the service quality components consisting of direct evidence (tangibles), reliability, responsiveness, assurance, and empathy influence the satisfaction of KUR product debtors at PT Bank BNI (TBK) KC Bandung? The purpose of this study is to study, find out, and analyze the influence of service quality components consisting of direct evidence (tangibles), reliability, responsiveness, assurance, and empathy on the satisfaction of KUR product debtors at PT Bank BNI (TBK) KC Bandung. The method used in this study is an explanatory survey, while the technical data analysis, namely validity test, reliability test, descriptive statistics, Inductive Statistical Analysis with Multiple Regression. The results of the study inform that (1) Direct evidence (tangibles) has a positive effect on debtor satisfaction. This means that if direct evidence (tangibles) is increased, then debtor satisfaction will also increase. (2) Reliability has a positive effect on debtor satisfaction. This means that if reliability is increased, then debtor satisfaction will also increase. (3) Responsiveness has a positive effect on debtor satisfaction. This means that if responsiveness is increased, then debtor satisfaction will also increase. (4) Assurance has a positive effect on debtor satisfaction. This means that if direct evidence (tangibles), reliability, responsiveness, assurance and empathy are increased, then debtor satisfaction will also increase. (5) Empathy has a positive effect on the level of debtor satisfaction. This means that if empathy is increased, then debtor satisfaction will also increase. (6) Direct evidence (tangibles), reliability, responsiveness, assurance and empathy have a positive effect on debtor satisfaction. This means that if direct evidence (tangibles), reliability, responsiveness, assurance and empathy are increased, then debtor satisfaction will also increase.